Fading distributions and co-channel interference in wireless systems. - Yacoub, Michel Daoud (IEEE Antennas & propagation magazine.)
This paper describes the physical models behind the various fading distributions applicable in wireless-communications systems, and presents the probability density functions, both for the signal envelope and for the power of the mobile radio signal. It addresses the problem of co-channel interference in terms of its mean value, for macrocellular and microcellular structures, and illustrates how the outage probability is influenced by a series of factors such as reuse pattern, modulation scheme, traffic load, and others.